2010
DOI: 10.1007/s11258-010-9848-0
|View full text |Cite
|
Sign up to set email alerts
|

Use of precise spatial data for describing spatial patterns and plant interactions in a diverse Great Basin shrub community

Abstract: Community-structuring processes continue to be of great interest to plant ecologists, and plant spatial patterns have been linked to processes including disturbance, dispersal, environmental heterogeneity, and plant interactions. Under the assumption that the analysis of the spatial structure of plant communities can help to elucidate the type and importance of the predominant community-structuring processes, many studies have analyzed point pattern data on various plant species. A variety of methods have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 46 publications
(85 reference statements)
2
20
0
2
Order By: Relevance
“…The aggregated patterns found in subzone El are similar to those observed in other stressful environments such as semi-arid shrublands (Rayburn et al, 2011) and savannas (Schleicher et al, 2011), and high-mountain communities (Fajardo et al, 2008). We also detected an increase in aggregation over the study period, as found by Malkison and Kadmon (2007), and Felinks and Wiegand (2008) in early successional communities.…”
Section: Erosional Subzonessupporting
confidence: 86%
“…The aggregated patterns found in subzone El are similar to those observed in other stressful environments such as semi-arid shrublands (Rayburn et al, 2011) and savannas (Schleicher et al, 2011), and high-mountain communities (Fajardo et al, 2008). We also detected an increase in aggregation over the study period, as found by Malkison and Kadmon (2007), and Felinks and Wiegand (2008) in early successional communities.…”
Section: Erosional Subzonessupporting
confidence: 86%
“…Krascheninnikovia lanata showed a non constant intensity within the study plot with some gaps in its distribution (Fig. 1; Rayburn et al 2011), but the detection of the accumulator effect under the heterogeneous null model suggests that habitat association contributes only weakly to the local accumulation of species richness in K. lanata neighborhoods. Repeating the same analyses without considering the focal species in the calculation of the ISAR curve revealed no significant departures from the null model (Table 1; Supplementary material Appendix 1).…”
Section: Resultsmentioning
confidence: 92%
“… Map of study plot (39 × 39 m), showing locations of all shrub individuals (upper left) and maps detailing the locations of individuals from each of the five shrub species. Figure adapted from Rayburn et al (2011). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, this issue is especially relevant and common in semi and semi-arid shrub lands [11,21,22]. Aggregated plant patterns in semiarid shrub lands have been variously attributed to facilitation [21,23,24], habitat heterogeneity [25], disturbance [26] and localized seed dispersal [27].…”
Section: Spatial Patternsmentioning
confidence: 99%